Role of iron in the nitric oxide-mediated fungicidal mechanism of ifn-γ-activated murine macrophages against Paracoccidioides brasiliensis conidia (2007)
ABSTRACT: Iron is an essential growth element of virtually all microorganisms and its restriction is one of the mechanisms used by macrophages to control microbial multiplication. Paracoccidioides brasiliensis, the agent of paracoccidioidomycosis, an important systemic mycosis in Latin America, is inhibited in its conidia-to-yeast conversion in the absence of iron. We studied the participation of iron in the nitric oxide (NO)-mediated fungicidal mechanism against conidia. Peritoneal murine macrophages activated with 50U/mL of IFN-γ or treated with 35 µM Deferoxamine (DEX) and infected with P. brasiliensis conidia, were co-cultured and incubated for 96 h in the presence of different concentrations of holotransferrin (HOLO) and FeS04 . The supernatants were withdrawn in order to assess NO2 production by the Griess method. The monolayers were fixed, stained and observed microscopically. The percentage of the conidia-to-yeast transition was estimated by counting 200 intracellular propagules. IFN-γ-activated or DEX-treated Mθs presented marked inhibition of the conidia-to-yeast conversion (19 and 56%, respectively) in comparison with non-activated or untreated Mθs (80%). IFN-γ-activated macrophages produced high NO levels in comparison with the controls. Additionally, when the activated or treated-macrophages were supplemented with iron donors (HOLO or FeSO4 ), the inhibitory action was reversed, although NO production remained intact. These results suggest that the NO-mediated fungicidal mechanism exerted by IFN-γ-activated macrophages against P. brasiliensis conidia, is dependent of an iron interaction.